PETA PIKIRAN SEBAGAI APERSEPSI DARI ABSTRAK KE KONKRET MENUJU KEBERMAKNAAN BELAJAR - Aly Mahfud (Universitas Islam Malang, 2021)
Bringing meaning to learning is one of the cores of teaching. To achieve that, it is necessary to bring meaningfulness in learning, namely linking learning materials with the reality experienced by students and providing a fulcrum on usefulness. That way, learning can be accepted by students. One of the things that Ausabel emphasizes is to provide a firm link in learning to turn the abstract into the concrete. Mind map as an apperception is an idea that qualifies to realize the usefulness of learning. This study uses a literature research design to answer (1) how important is apperception in meaningful learning? and (2) how mind maps are used as the main activity in apperception when starting learning to realize meaningful learning? with a literature research design, the research answers are obtained as follows: (1) Apperception is important in early learning activities as a link between new topics and students' previous experiences as well as the usefulness of topics in real life. (2) Mind maps as apperception facilitate learners to relate their experiences and get an explanation of the usefulness of the material for themselves. These two main points are in accordance with Ausabel's goal of developing a meaningful learning theory.